2012
DOI: 10.1523/jneurosci.0337-12.2012
|View full text |Cite
|
Sign up to set email alerts
|

Novel Allosteric Agonists of M1 Muscarinic Acetylcholine Receptors Induce Brain Region-Specific Responses That Correspond with Behavioral Effects in Animal Models

Abstract: M1 muscarinic acetylcholine receptors (mAChRs) represent a viable target for treatment of multiple disorders of the central nervous system (CNS) including Alzheimer’s disease and schizophrenia. The recent discovery of highly selective allosteric agonists of M1 receptors has provided a major breakthrough in developing a viable approach for discovery of novel therapeutic agents that target these receptors. Here, we describe the characterization of two novel M1 allosteric agonists VU0357017 and VU0364572 that dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
137
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(145 citation statements)
references
References 45 publications
4
137
0
1
Order By: Relevance
“…Although previous studies indicate that activation of M 1 mAChRs is critical for learning, memory, and executive functions, the role of M 4 mAChRs in modulating cognitive function remains unclear Shirey et al, 2009;Digby et al, 2012;Ma et al, 2009). We found that VU0152100 alone had no effect on PPI or the acquisition of contextual fear conditioning, suggesting that M 4 may not be required for normal hippocampal learning and memory processes in young adult rats.…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…Although previous studies indicate that activation of M 1 mAChRs is critical for learning, memory, and executive functions, the role of M 4 mAChRs in modulating cognitive function remains unclear Shirey et al, 2009;Digby et al, 2012;Ma et al, 2009). We found that VU0152100 alone had no effect on PPI or the acquisition of contextual fear conditioning, suggesting that M 4 may not be required for normal hippocampal learning and memory processes in young adult rats.…”
Section: Discussionmentioning
confidence: 55%
“…However, as the higher doses of amphetamine used in the cognitive studies can induce increases in both dopamine and norepinephrine (McKittrick and Abercrombie 2007), it will be important in future studies to confirm that these effects of VU0152100 are mediated predominately through reversal of dopaminergic signaling. Finally, VU0152100 provides an important M 4 -selective tool compound that used along with recently reported M 1 -selective PAMs (Ma et al, 2009;Shirey et al, 2009) or allosteric agonists (Lebois et al, 2010;Digby et al, 2012) will allow a more complete understanding of the relative roles of these two mAChR subtypes in regulating multiple aspects of cognitive function.…”
Section: Discussionmentioning
confidence: 99%
“…136 Studies in native tissues of M 1 mAChR-mediated responses demonstrate that while both compounds potentiate NMDA receptor currents in hippocampal pyramidal cells and induce hippocampal LTP, they are devoid of electrophysiological activity in PFC pyramidal cells. These observations correlate well with the aforementioned study in which VU0357017 demonstrated efficacy in CFC, a hippocampal-dependent animal model of cognition.…”
Section: ■ M 1 Machr-selective Ligandsmentioning
confidence: 99%
“…These data are consistent with the hypothesis that changes in mAChR signaling could contribute to the symptoms observed in schizophrenia patients. Of the five mAChR subtypes (M 1 -M 5 ), M 1 is the predominant mAChR subtype expressed in the PFC (Levey et al, 1991) and likely participates in induction of mLTD (Caruana et al, 2011) and other physiological responses that are important for PFC-dependent cognitive functions (Digby et al, 2012;Shirey et al, 2009). We now report discovery and optimization of VU0453595 as a novel, highly selective positive allosteric modulator (PAM) for M 1 that provides excellent pharmacokinetic properties and brain exposure in mice after systemic administration.…”
Section: Introductionmentioning
confidence: 99%